Food consumption, nutritional intakes and the role of milk formulas in nutrient adequacy among young children from birth to 2 years living in urban Algeria - Alice Busnel; Marine Domet; Khaoula Ramchani Ben Othman; Caroline Desclée De Maredsous; Hanane Ghomari-Boukhatem; Malika Bouchenak; Karim Bouziane-Nedjadi; Peggy Drouillet-Pinard (Cambridge University Press, 2023)
Abstract Objective: Undernutrition, stunted growth and obesity remain a concern in Algeria. Currently, limited data are available on nutrient intakes among children. Our study aimed to describe food and nutrient intakes and the role of milk formulas among Algerian children. Design: Dietary intakes were collected using a 4-d interview-based survey for children aged 0-24 months, living in urban areas in Algeria in 2019. Setting: Food consumptions were described. For children aged 6-24 months, nutrient intakes and adequacy were estimated. Modelling was used to estimate the nutritional impact of substituting cow's milk for age-appropriate infant formulas (IF). Participants: Totally, 446 children aged 0-24 months. Results: Before 6 months, 91·6 % of infants were breastfed. Breastmilk was also the main milk consumed between 6 and 12 months, whereas cow's milk predominated after 12 months. In children aged 6-24 months, nutrient adequacy prevalence was above 75 % for the majority of nutrients. However, less than 30 % of the children had adequate intakes for total fats, Fe and vitamin D. Simulated substitution of cow's milk for IF led to improved adequacy for proteins, Fe, and vitamins D and E. Conclusions: Our study showed that breast-feeding rates were high until 6 months, then declined with age. Consumed foods allowed Algerian children aged 6-24 months to meet most of their nutritional needs, but inadequate intakes were reported for some key nutrients. Our modelling suggested that milk formulas may help to improve nutrient adequacy among non-breastfed infants. Other dietary changes could also be further investigated to enable children to meet all nutritional recommendations.